44.7k views
4 votes
Question 6 of 10 If you apply the changes below to the linear parent function, (x) = x, what is the equation of the new function? Vertically stretch by a factor of 3. Flip over the x-axis. A. g(x) = - 3* g X B. g(x) = 3x - 1 O c. g(x) = -3x G D. g(x) =

Question 6 of 10 If you apply the changes below to the linear parent function, (x-example-1
User Suleman C
by
4.9k points

1 Answer

7 votes

The given function is


f(x)=x

If f(x) is stretched vertically by a factor of 3 the function will become


h(x)3x

If the function is then flipped over x-axis

The function will give


p(x)=-3x

Therefore, If f(x) is stretched vertically by a factor of 3 and flipped over the x-axis

The result is


g(x)=-3x

User Rasmus Kaj
by
5.3k points